Moderate Intensity Aerobic Exercise Potential Favorable Effect Against COVID-19: The Role of Renin-Angiotensin System and Immunomodulatory Effects - Arazi, Hamid; Falahati, Akram; Suzuki, Katsuhiko (Frontiers in Physiology, 2021)
The COVID-19 pandemic is caused by a novel coronavirus (CoV) named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). As the angiotensin converting enzyme 2 (ACE2) is the cellular receptor of SARS-CoV-2, it has a strong interaction with the renin angiotensin system (RAS). Experimental studies have shown that the higher levels of ACE2 or increasing ACE2/ACE1 ratio improve COVID-19 outcomes through lowering inflammation and death. Aerobic physical exercise fight off infections by two mechanisms, the inhibition of ACE/Ang II/AT1-R pathway and the stimulation of ACE2/Ang-(1-7)/MasR axis. Exercise can also activate the anti-inflammatory response so that it can be a potential therapeutic strategy against COVID-19. Here, we summarize and focus the relation between COVID-19, RAS and immune system and describe the potential effect of aerobic moderate intensity physical exercise against coronavirus as a useful complementary tool for providing immune protection against SARS-CoV-2 virus infection which is a novel intervention that requires further investigation.